Impact of cultivation technologies elements on winter wheat grain productivity and quality - К. М. Олійник; Г. В. Давидюк; Л. Ю. Блажевич; Л. В. Худолій (Plant Varieties Studying and Protection)
Purpose. To develop and improve adaptive technologies of winter wheat cultivation which provide high productivity and quality of grain. Methods. Field and laboratory studies, mathematical and statistical analysis. Results. During 2011–2015, the impact of cultivation technologies on the formation of grain quality and yield of winter wheat variety ‘Stolychna’ (with pea as predecessor) was studied. When using alternative technologies with only predecessor by-products application, the yield of winter wheat with integrated crop protection system was 4,56 t/ha, with minimal protection – 4.25 t/ha with grain quality of the 5th class of B group. Resource saving cultivation technologies with limited application of fertilizers (Р45К45N30(II)+30(IV)) provided productivity at the level of 4,87–5,50 t/ha with grain quality of the 2nd–3rd class of A group. Grain yield of 6.01 t/ha with indicators of the 2nd–3rd class of quality was obtained with the use of intensive cultivation technology with application of mineral fertilizers (Р90К90N30(II)+60(IV)+30(VIII)) on the background of applying predecessor’s by-products and integrated crop protection. The highest yield of grain (6.22 t/ha) with indicators of the 2nd class of A group quality on average for the research period was provided by energy-intensive technology, that requires the application of mineral fertilizers (P135K135N60(II)+75(IV)+45(VIII)) and incorporation of predecessor’s by-products in the soil, and integrated plant protection. Conclusion. It was found that in the northern part of the Right-Bank Forest-Steppe zone of Ukraine, the highest productivity of winter wheat was obtained in dark grey podzolic soils when using the energy-intensive technology with application of P135K135N60(II)+75(IV)+45(VIII) on the background of predecessor’s by-products and integrated crop protection. This technology ensured the grain yield of 6.22 t/ha of the 2nd class of A group quality.